Sudden Death Secondary to an Undiagnosed B‐Cell Lymphoma of the Hypopharynx and Infiltration of the Inferior Constrictor Muscle1. Issue 4 (3rd October 2017) - Lo Pinto, Sara; Barranco, Rosario; Cuccì, Maria; Caputo, Fiorella; Fossati, Francesca; Orcioni, Giulio Fraternali; Ventura, Francesco
Abstract: The aim of this presentation was to share an uncommon form of sudden death, suffered by a 64‐year‐old woman, due to a mechanical obstruction of hypopharynx by an undiagnosed B‐cell lymphoma, infiltrating the inferior pharyngeal constrictor muscle. A forensic approach by means of scene investigation, circumstantial data collection, autopsy, and histological and toxicological investigations led to conclude that the cause of death was asphyxia, correlated with B‐cell lymphoma of the hypopharynx. The autopsy examination highlighted the presence of a wall thickening, infiltrating, and projecting into the hypopharynx lumen. The histological analysis showed the essential finding of a B‐cell lymphoma of the hypopharynx, diffusely infiltrating the inferior pharyngeal constrictor muscle. To conclude, this case demonstrates once more that in the absence of specific data, a thorough forensic investigation including autopsy, histological examination, and circumstantial data collection is mandatory to reach a correct cause of death.